Negotiating artefacts: student game creation for education and introspection - Jerrett, Adam (Frontiers in Computer Science, 2024)
Learning through gameplay is being increasingly adopted by educators, who integrate games into academic curricula to address complex subjects. “Existential” game design is recognised as a practice for personal growth, self-reflection, and therapy, though it has been underexplored in educational contexts. The research thus describes the creation and deployment of two game design assessments for a private higher-education institution in South Africa that allowed undergraduate students to explore various complex topics. The research utilized an action research approach with a pre-test/post-test design for data collection, with results being explored using sentiment-based and thematic analysis. The findings reveal mixed responses from participants which highlighted the usefulness of the exercise but noted that the courses’ focus on technical quality and a lack of adequate preparation hindered the experience, with adequate mentoring and developer support being suggested to improve it. Arts-based approaches to such educational interventions, with a focus on “deep” games, critical play, and values-conscious design throughout the curriculum, are discussed as a potential solution. While game design remains a useful educational tool for engaging with complex societal issues, educators must increasingly ensure they prepare undergraduate students adequately for such creative exercises.